DIFFERENCE BETWEEN TRANSLATE AND INTERPRET («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Difference between translate and interpret may not be easy to grasp at once as they both speak about putting an idea from one language to another language. The words translate and interpret are common words in English language. While translate means to write a sentence or statement in one language in another language, interpret means to explain the meaning of spoken words of a person. Both translation and interpretation are very important though two different linguistic capabilities, and there is a great demand all over the world for both these professionals; namely, translators and interpreters. However, owing to similarities, there is confusion in the minds of people regarding translate and interpret. This article intends to make these differences clear to understand the two professions and the abilities better.
Keywords: The term of translate, the process of interprete, oral translation, written translation.